The Utilization of Phonics Songs in Phonics Reading Classes in Indonesia: Teachers’ Perspectives - Setyo Utami; Bachrudin Musthafa (Universitas Pendidikan Indonesia, 2022)
The use of phonics approaches for teaching early reading skills to young learners in Indonesian EFL classes seems to be on the rise. However, as phonics relies on students’ ability in corresponding letters and the sounds of the letters, the fact that the English pronunciation for the alphabet is different from that of Bahasa Indonesia could be an obstacle in a way that it might lead students to confusion. To cope with this problem, some teachers are found to have applied phonics songs in order to help their young learners. This paper aims to report teachers’ perspectives on their experiences in utilizing phonics songs to help young learners in Indonesia develop their early reading skills. A case study is employed by using instruments of questionnaires and interviews involving 20 EFL teachers in Indonesia. The results show the teachers’ positive perspectives on the utilization of phonics songs in early reading classes as well as its benefits and drawbacks which can be aspects that teachers should seriously consider when choosing the most suitable phonics songs to be applied in young learners’ classes in Indonesia.